Flood Risk Spatial Modeling Based on Geographical Information Systems and Remote Sensing in the Pemangkat Regensi - Ajun Purwanto; Paiman Paiman (Jurnal Penelitian Pendidikan IPA, 2023)
Flood is a disaster that occurs every year in Indonesia with various risks. This study aims to create a spatial model of flood risk and determine the distribution of flood risk in Pemangkat, Sambas Regency. The method used is surveying and interpreting secondary data from the Digital Elevation Model, topographic maps, and land cover images. The data collected includes area, elevation, slope, distance from the river, land use, and rainfall. The tool used is a set of Geographic Information System tools, namely Arcgis 10.8. Data analysis using Weighted Sum for generated Flood risk map and Geographically Weighted Regression for flood risk spatial modeling. The results showed that the Pemangkat sub-district had flood risk classes, namely very low, low, moderate, high, and very high classes. Very high to high flood-risk classes are spread in the cities of Pemangkat and Sabatuan. In contrast, medium to deficient classes are spread in Jelutung, Gugah Sejahtera, Penjajap, Harapan, Lonam, and Parapakan. Very low flood risk area is 8.17 ha (8.16%), low 16.97 ha (16.97%, medium 28.17 ha (28.16%), high 32.28 ha (32.28%) and very high 14.41ha (14.39%). The values obtained from the analysis show that GWR modeling is excellent because R2 is relatively tiny, 0.39.